The aggrecan expression post platelet rich fibrin administration in gingival medicinal signaling cells in wistar rats (rattus novergicus) during the early osteogenic differentiation (in vitro) - Alexander Patera NUGRAHA; Ida Bagus NARMADA; Diah Savitri ERNAWATI; Aristika DINARYANTI; Eryk HENDRIANTO; Igo Syaiful IHSAN; Wibi RIAWAN; Fedik Abdul RANTAM (Veteriner fakultesi dergisi, 2019)
Platelet Rich Fibrin (PRF) is rich for growth factors which can improve the Gingival Medicinal Signaling Cells" (GMSCs) osteogenic differentiation. Aggrecan is chondrogenic differentiation marker which has a significant role in the early stage of GMSCs" osteogenic differentiation. This study aimed to analyze the expression of Aggrecan post PRF administration on the osteogenic differentiation in vitro. This research is a true experimental study using the post-test only control group design with a simple random sampling. GMSCs were isolated from the lower gingival tissue of healthy male Wistar rats (Rattus novergicus) (n=4), weighted around 250 g, a month old, then cultured for 2 weeks and passaged for 4-5 days. GMSCs in the passage 3-5 were cultured in five M24 plates (N=54; n=6/group) for 7 days, 14 days, and 21 days in three different culture mediums, they were negative control group which included α Modified Eagle Medium; positive control group which contained High Glucose-Dulbecco"s Modified Eagle Medium (DMEMHG) combined with osteogenic medium; and at last, treatment group which were DMEM-HG combined with both osteogenic medium and PRF. A one-way Analysis of Variance (ANOVA) test (P<0.05) was performed. The treatment group showed the highest Aggrecan expression of 16.15±2.15 on the 7th day. The lowest Aggrecan expression with a value of 3.67±0.76 on the 21th day occurred in the negative control group. There was a significant difference of Aggrecan expression between groups (P<0.05). PRF administration unexpectedly stimulates Aggrecan expression of GMSCs during the osteogenic differentiation that useful to accelerate the bone remodeling or neo-cartilage formation.